Herbicide selection for weed control in cassava (Manihot esculenta Crantz) in Bolivar, Colombia - Luna-Castellanos, Lily Lorena; Espinosa-Carvajal, Manuel Ramón; De-La-Ossa-Albis, Víctor Alfonso; Panza-Tapia, Blas Dagor; Garcia-Peña, Joaquin Alfonso (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Cassava is the most important tuberous root for food security in the Department of Bolívar (Colombia); however, inefficient weed management during early growth stages has reduced productivity, generating profit losses for farmers in this region. Therefore, this research aimed to select herbicides for weed control. At Carmen de Bolívar de Corpoica, a completely randomized block design was used with three repetitions, evaluating the herbicide mixtures linuron + pendimethalin, oxadiazon + diuron and metolachlor + atrazine in pre-emergence, and glufosinate ammonium, haloxyfop-p-ethoxyethyl and fluaxifop-p-butyl in post-emergence, along with a control treatment. The evaluated variables weed control efficiency, survival, degree of phytotoxicity, height, stem diameter and yield of fresh roots in cassava plants showed that the mixture metolachlor + atrazine applied in pre-emergence had the highest efficiency for weed control and cassava crop selectivity, obtaining a yield increase of 4.34 t ha-1, as compared to the manual control treatment. The results indicated the effectiveness of herbicides within integrated weed management in cassava crops on the Colombian Caribbean Coast.